2013
DOI: 10.1007/s10393-013-0835-5
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasmal Upper Respiratory Tract Disease Across the Range of the Threatened Mojave Desert Tortoise: Associations with Thermal Regime and Natural Antibodies

Abstract: Most research of upper respiratory tract disease (mycoplasmal URTD) in the threatened Mojave Desert tortoise (Gopherus agassizii) has worked under the hypothesis that the pathogen, Mycoplasma agassizii, has a relatively consistent and predictable effect on tortoise populations across their natural range. In contrast, we hypothesized that multiple factors influence the prevalence of disease and analyzed biological and environmental variables that vary significantly across the Mojave Desert. We used multiple reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 36 publications
0
45
1
Order By: Relevance
“…; Sandmeier et al . ). If the apparent majority of contacts in the wild have low transmission probability as we observed, low infection prevalence would be expected compared to a captive situation where contact rates and durations are amplified.…”
Section: Discussionmentioning
confidence: 97%
“…; Sandmeier et al . ). If the apparent majority of contacts in the wild have low transmission probability as we observed, low infection prevalence would be expected compared to a captive situation where contact rates and durations are amplified.…”
Section: Discussionmentioning
confidence: 97%
“…with respiratory disease in snakes, tortoises, and turtles (Penner et al, 1997;Jacobson et al, 1991a;Sandmeier et al, 2013;Guthrie et al, 2013). Geographically, M. tes tudineum seems to have a similar distribution to, but a lower prevalence than, M. agassizii in desert and gopher tortoises across North America.…”
Section: B Mycoplasmosismentioning
confidence: 96%
“…Geographically, M. tes tudineum seems to have a similar distribution to, but a lower prevalence than, M. agassizii in desert and gopher tortoises across North America. Mycoplasma exhibits interspecies transmission, and cold weather has been shown to decrease the resistance of Mojave desert tortoises to infection (Sandmeier et al, 2013). Mycoplasma exhibits interspecies transmission, and cold weather has been shown to decrease the resistance of Mojave desert tortoises to infection (Sandmeier et al, 2013).…”
Section: B Mycoplasmosismentioning
confidence: 99%
“…Sandmeier et al. () found a positive relationship between severe winter weather and markers of upper respiratory tract disease in Mojave Desert Tortoises ( Gopherus agassizii ). Additionally, telemetry studies have indicated that disease may be an important constraint on Gopher Tortoises ( Gopherus polyphemus ) during winter, when diseased individuals were found to leave their burrows during cold weather (McGuire et al., ).…”
Section: Introductionmentioning
confidence: 99%